Determinants of Tourism Growth in India: Analysing Economic and Environmental Factors Influencing Inbound and Domestic Tourism (2022–2023) - Praveen, M.; Ranjitha, R.; Selvi Tamil, R.; Dayana Jevalin, R. (Journal of Environmental Management and Tourism, 2026)
This research paper focuses on the tourism industry as a vital sector that plays a significant role in driving economic growth, generating employment opportunities, preserving cultural heritage, and strengthening international relationships. The study further explores the economic and environmental determinants that shape both inbound and domestic tourism in India. The research incorporates Pearson Correlation Matrix, Factor Analysis, and Multiple Linear Regression to analyse data sourced from government reports and articles for the year 2022. The top three countries from which India received the highest number of tourists in 2022 were the U.S.A, Bangladesh, and the U.K. Factor analysis revealed that 83.31% of total variance in tourism growth is explained by three major components, strongly linked to economic and disaster-related factors. The Kaiser-Meyer-Olkin (KMO) value was 0.668, confirming sampling adequacy, and Bartlett’s Test of Sphericity was significant (p = 0.000), validating the use of factor analysis. Pearson correlation results show a strong relationship between Inbound Tourism and State GDP (r = .772), and similarly between Domestic Tourism and State GDP (r = .767). Regression analysis revealed a strong predictive model with an R value of 0.84 for inbound tourism and 0.799 for domestic tourism. The study concludes that economic factors such as GDP growth and effective utilization of sanctioned tourism funds are vital drivers for tourism development in India, alongside the need for effective disaster management strategies.